Stem cells in Osteoporosis: From Biology to New Therapeutic Approaches - Vasilis Paspaliaris; George Kolios (Stem Cells International)
Osteoporosis is a systemic disease that affects the skeleton, causing reduction of bone density and mass, resulting in destruction of bone microstructure and increased risk of bone fractures. Since osteoporosis is a disease affecting the elderly and the aging of the world’s population is constantly increasing, it is expected that the incidence of osteoporosis and its financial burden on the insurance systems will increase continuously and there is a need for more understanding this condition in order to prevent and/or treat it. At present, available drug therapy for osteoporosis primarily targets the inhibition of bone resorption and agents that promote bone mineralization, designed to slow disease progression. Safe and predictable pharmaceutical means to increase bone formation have been elusive. Stem cell therapy of osteoporosis, as a therapeutic strategy, offers the promise of an increase in osteoblast differentiation and thus reversing the shift towards bone resorption in osteoporosis. This review is focused on the current views regarding the implication of the stem cells in the cellular and physiologic mechanisms of osteoporosis and discusses data obtained from stem cell-based therapies of osteoporosis in experimental animal models and the possibility of their future application in clinical trials.